Redesain Tempat Penyimpanan Sementara Limbah B3 Pada Pabrik Pembekuan Ikan PT. XYZ Kabupaten Surabaya - Evan Yafi Bachtiar; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The fisheries industry is undergoing rapid technological advancement, which has expanded across various regions in Indonesia, has the potential to increase the volume of waste generation, particularly hazardous and toxic waste. PT XYZ is one of many companies engaged in fish processing that generates a significant amount of B3 waste. The types of B3 waste stored by PT XYZ include used oil or lubricants, rusty iron, used wiping cloths (majun), used batteries, electronic waste, and containers/packaging contaminated with B3 waste residues. This study aims to evaluate current practices based on government regulations, identify the types and quantities of B3 waste generated, and redesign the TPS for B3 waste at PT XYZ in accordance with Minister of Environment and Forestry Regulation No. 6 of 2021. The research methods employed include observation, interviews, and the redesign of the B3 waste TPS in compliance with the aforementioned regulation. Based on the research, it was discovered that the company has not fully implemented the applicable regulations for example, the use of used oil containers as B3 waste packaging. Therefore, improvements are necessary in the procedures for B3 waste storage. A redesign of the TPS is essential to ensure that waste management activities align with existing legal standards.